Plastically deformed La–Fe–Si: Microstructural evolution, magnetocaloric effect and anisotropic thermal conductivity. (1st April 2020) - Ouyang, Yi; Zhang, Mingxiao; Yan, Aru; Wang, Wen; Guillou, Francois; Liu, Jian
Abstract: La(Fe, Si)13 -based alloys are considered to be one of the most promising magnetocaloric materials for solid state cooling. However, the intrinsic brittleness of NaZn13 -type functional phase (1:13 phase) obstructs the shaping of La–Fe–Si alloys into desired geometries for the applications in magnetic cooling devices. Here, by exploiting the excellent deformability of α-Fe phase, we propose a near-net shaping method of open die-forging to prepare La–Fe–Si thin plates. This novel approach is demonstrated for the first time to exhibit several advantages including producing full-dense materials, facilitating the phase formation, and maintaining large magnetocaloric effect. The microstructural and texture evolution have been systematically investigated for the pre-deformed and annealed La–Fe–Si alloys. Large magnetic entropy change of 14 J/kg K at 2 T is obtained in the annealed sample and 11 J/kg K for the hydrogenated sample without hydrogen-induced cracking. Furthermore, a unique dual-phase structure consisting of aligned α-Fe phase and non-equiaxial 1:13 grains brings about the significant anisotropic thermal conductivity in cross-plane and in-plane directions for the plastically-deformed plates. This new insight would greatly benefit the design of high efficient magnetic refrigerator with one-way enhanced thermal conduction. Graphical abstract: Image, graphical abstract